Sosialisasi Dan Pelatihan Untuk Mengoptimalisasikan Pembuatan Format Surat Resmi Dalam Organisasi Intra Sekolah Menggunakan Microsoft Word Bagi Pengurus Osis Smp Negeri 1 Patikraja - Indah Ayuningtiyas; Bunga Lare Javanie; Maulida Citra Fajriani; Mohammad Dava Ghozan Alvareza; Ito Setiawan (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Inconsistent official letter formats within the student organization of SMP Negeri 1 Patikraja often hinder professional administration and cause the organization to forget important things when new leadership takes over. The purpose of this activity was to improve the student council (OSIS) administrators' ability to write official letters by teaching them how to use Microsoft Word technical features. The implementation method involved socializing theory about writing rules and hands-on training covering the use of headers and footers, mail merge, and building blocks. Evaluation results showed that participants' skills improved significantly, with the ability to use mail merge independently increasing from 5% to 76.2%. All participants (100%) responded positively regarding the relevance of the material to the organization's needs. It was concluded that standardizing digital letter formats can improve the efficiency of student bureaucracy and ensure the consistency of the institutional identity of the ISO 9001:2000-certified school.